An Analysis on COVID-19 Disinformation Triangle in Indonesia - Senja Yustitia; Panji Dwi Ashrianto (Komunikator, 2020)
Misinformation and disinformation are widespread in society, as well as during the outbreak of COVID-19. Much of this information is partly accurate, but the others are not, making it difficult for people to find reliable sources and guides. This study aims to see the tendency of misinformation and disinformation related to COVID-19, which has been fact-checked by Mafindo in January - July 2020 period using quantitative content analysis.  The misinformation and disinformation criteria refer to the seven UNESCO types.  They were analyzed using the disinformation triangle model by Victoria L. Rubin. The results showed that the highest intensity of COVID-19 misinformation and disinformation was in March, April, and May. Misinformation and disinformation are mostly disseminated through the platforms like Facebook, Twitter, and WhatsApp. The types of content that are most widely shared are misleading content, fabricated content, and false context. Besides, personal opinions are also the source of the most common COVID-19 misinformation during January-July 2020.